The Implicated Roles of Cell Adhesion Molecule 1 (CADM1) Gene and Altered Prefrontal Neuronal Activity in Attention-Deficit/Hyperactivity Disorder: A “Gene–Brain–Behavior Relationship”? - Jin, Jiali; Liu, Lu; Chen, Wai; Gao, Qian; Li, Haimei; Wang, Yufeng; Qian, Qiujin (Frontiers in Genetics, 2019)
Background: Genes related to cell adhesion pathway have been implicated in the genetic architecture of Attention-Deficit/Hyperactivity Disorder (ADHD). Cell adhesion molecule 1, encoded by CADM1 gene, is a protein facilitating cell adhesion, highly expressed in the human prefrontal lobe. This study aimed to evaluate the association of CADM1 genotype with ADHD, executive function, and regional brain functions. Methods: The genotype data of 10 tag SNPs of CADM1 for 1,040 children and adolescents with ADHD and 963 controls were used for case-control association analyses. Stroop Color–Word Interference Test, Rey–Osterrieth complex figure test (RCFT) and Trail Making Test (TMT) were conducted to assess ‘inhibition’, ‘working memory’ and ‘set-shifting’ respectively. A subsample (35 ADHD versus 56 controls) participated in the nested imaging genetic study. Resting-state functional magnetic resonance images (rs-fMRI) were acquired and the mean amplitude of low-frequency fluctuations (mALFF) were captured. Results: Nominal significant genotypic effect of rs10891819 in ‘ADHD-alone’ subgroup was detected (P=0.008) with TT genotype as protective. The results did not survive multiple testing correction. No direct genetic effect was found for performance on executive function tasks. In the imaging genetic study for the ‘ADHD-whole’ sample, rs10891819 genotype was significantly associated with altered mALFF in the right superior frontal gyrus (rSFG, peak t=3.85,corrected P<0.05). Specifically, the mALFFs in T-allele carriers were consistently higher than GG carriers in ADHD and control groups. Endophenotypic correlation analyses indicated a significant negative correlation between ‘Word Interference Time’ in Stroop (shorter ‘Word Interference Time’ indexing better inhibitory function) and mALFF in the rSFG (r=-0.29, P=0.006). Finally, mediation analysis confirmed significant indirect effects from ‘rs10891819 genotype (T-allele carriers)’ via ‘mALFF (rSFG)’to ‘Inhibition (‘Word Interference Time’)’[Sobelz=-2.47; B=-2.61, 95% CI=(-0.48 to -4.72); P=0.009]. Conclusions: Our study offered preliminary evidence to implicate the roles of CADM1 in relation to prefrontal brain activities, inhibition function and ADHD, indicating a potential ‘gene-brain-behavior’ relationship of the CADM1 gene.. Future studies with larger samples may specifically test these hypotheses generated by our exploratory findings.